Environment Protection in Israel - N. S. Orlovsky; L. G. Orlovsky; I. S. Zonn (Проблемы постсоветского пространства)
In such country as Israel with its high industrialization and urbanization rates the environment protection is of key importance for preserving the biodiversity of nature. Awareness of the need to protect precious natural resources and landscapes of Israel forced to pass numerous laws on protection of nature and wild animals. These laws provide legal basis for protection of environment, natural resources, wild animals, unique nature features and places being of scientific and educational value in this country.Israel locates at the juncture of three continents combining different climatic and botanical regions which have led to appearance of the unique, by diversity and composition, plant and animal world. In Israel you can find 2800 plant varieties (of which 150 are endemics), 8 species of amphibia, 80 species of reptiles, 450 species of birds and 70 species of mammals. For protection of natural biodiversity there were established 224 nature preserves and 203 and historical heritage deserves special mention.In the recent years the governmental and public organizations have focused on development of the programs on environment management for monitoring and ensuring the required quality of water and air and for processing and utilization of solid wastes.Quite spectacular achievements are observed in reintroduction of predatory and bible species, protection of sea turtles, impoundment of the Hula valley and preservation of migratory birds. The government’s initiatives were welcomed by the public that joined in national parks which cover around 23% of the territory of Israel. The nature preserves and national parks represent the whole range of the natural heritage of Israel: Mediterranean forests, coastal and water landscapes, sand dunes, desert and crater landscapes and oases, while the unique archeological these activities. The environmental education, awareness and activities of the society have increased enormously which is proved by the growing number of nongovernmental environmental organizations — from a few in the 1990s to over one hundred nowadays. The greater attention is paid to collection and publication of environmental data.